The Relationship Between Smartphone Overuse, Affective Lability, Depression, and Anxiety Levels in University Students - Doğan, Veysel; Kavak Sinanoğlu, Gökçe (The European Research Journal, 2026)
Objective: This study aimed to investigate the relationship between smartphone overuse and affective lability, depression, and anxiety levels among university students.Methods: A total of 216 university students were included in the study. Participants were recruited via online platforms. To collect data, sociodemographic data forms, the Affective Lability Scale-18 (ALS-18), the Patient Health Questionnaire-9 (PHQ-9), the Generalized Anxiety Disorder-7 (GAD-7), and the Smartphone Overuse Screening Scale (SOSS) were used.Results: The mean age of the 216 university students who participated in the study was 21±1.23 years; 141 (65.28%) were male, 75 (34.72%) were female; 6 (2.78%) were only children, while 210 (97.22%) had siblings. Fourteen (6.48%) had parents living separately, and 202 (93.52%) had parents living together. Spearman correlation analysis revealed a significant positive correlation between the total score of the SOSS and the total score, as well as all subdimensions of the ALS-18, and the total scores of the PHQ-9 and GAD-7. Wilcoxon test showed no significant difference in total SOSS scores between male and female groups, between only children and those with siblings, or between those who had received psychological treatment and those who had not. The Wilcoxon test indicated that participants with siblings scored significantly higher in the ALS-18 Depression/Elevation subscale compared to those who were only children. Regression analysis results showed that among the independent variables, only the ALS-18 anger variable had a significant effect on smartphone overuse.Conclusion: Smartphone overuse is associated with affective lability, anxiety levels, and depressive symptoms. Therefore, there is a need for appropriate health education programs and interventions to improve the mental health of university students.